Visual Order and the Creation of Artistic Ambience in Realistic Composition of Ink-and-Wash Figure Painting - Li, Na; Tsetsegdelger D. (International Journal of Social Sciences and Public Administration, 2026)
Since the introduction of realistic modeling concepts into ink-wash figure painting, the composition of these works has undergone a profound restructuring of visual order. From a formal analysis perspective, this paper explores how realistic composition seeks a balance between traditional Chinese compositional principles and Western concepts of realistic space, and further analyzes how this restructuring of visual order influences the generation and transformation of the work’s artistic atmosphere. The study argues that the realistic composition in contemporary ink-wash figure painting has formed a unique logic of “form-structure-meaning”-establishing a rational visual order through focal perspective, proportional relationships, and spatial layers, while simultaneously creating a poetic, atmospheric space through traditional techniques such as negative space, the interplay of solid and void, and variations in density. This fusion of dual structures enables realistic figure painting to transcend the limitations of objective representation, achieving an aesthetic realm where the “visible” and the “sensible” are unified.